Portable Environmental Monitoring System using IOT (PEMS) - Rokhmad, Zul Helmy Izzani; Mohd Shah, Shaharil (Journal of Electronic Voltage and Application, 2024)
Air pollution, which is a major health and environmental hazard, is caused by various factors such as industrial, transportation, and domestic activity. The Air Quality Index (AQI) is used as an indication of air quality and potential health dangers to increase public awareness. This work proposed a Portable Environmental Monitoring System using IoT (PEMS) to monitor the air quality parameters and mapping them to the AQI rating and CO2 concentration. PEMS performs three major functions which are to measure the particulate matters, carbon dioxide (CO2) concentration and flammable gases. The Blynk application is used for the monitoring of the gathered data, which is also stored in its database. The values of PM1, PM2.5 and PM10 in μg/m3 are measured by using PMS5003 Particulate Matter. Meanwhile, the CO2 concentrations are obtained by using MQ-135 Air Quality sensor and flammable gases such as Butane and Propane are detected by using the MQ-6 Gas sensor. Based on the experiments, Parit Raja Industrial Estate exhibits the highest average of PM1, PM2.5 and PM10 values due to its industrial surroundings. TDI Residential College comes second due to tenant occupancy and smoking activities. Conversely, PTTA Library at UTHM has the lowest PM values due to its spacious area and good air circulation. In terms of CO2 concentration, Parit Raja Industrial Estate records the highest values due to anthropogenic CO2 influence, while TDI Residential College follows closely, influenced by tenant exhalation and poor air circulation. Meanwhile, the PTTA Library, UTHM maintains the lowest CO2 concentration due to its spacious area and efficient air circulation. Therefore, it is shown, based on the results, that PEMS has provided vital data on air quality parameters, thereby contributing pivotal information to assess the environmental health status, particularly in terms of the AQI.